DESIGN AND DEVELOPMENT INFORMATION SYSTEM CODIFICATION OF THE NAVY INSUPPORT PLANNING MAINTENANCE SYSTEM (PMS) - Hariyanto Hariyanto; Budisantoso Wirjodirjo; Ayip Rivai (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2021)
Republic of Indonesia warship is one of the main elements in the Integrated Fleet Weapon System (SSAT) owned by the Indonesian Navy. Republic of Indonesia warship must have combat readiness so that it is always ready to carry out exercises and operations according to its main tasks. Combat readiness can be achieved thanks to good logistical support. The codification information system is an important part of the automation of debriefing at Dopusbektim in providing computerized logistical support. With the codification information system, it is hoped that the user unit will be easier and can shorten the processing time of requests at the depot warehouse. The research objective is the development of existing applications by designing a codified information system application using the Quality Function Deployment (QFD) and System Development Life Cycle (SDLC) methods, so that it is expected to solve existing problems. Through interviews and questionnaires obtained 12 attributes. The 12 selected attributes above are then processed using the Quality Function Deployment (QFD) method in the House of Quality (HOQ) matrix so that the highest technical importance value is obtained, namely the integrated technical response with the Codification Subdistribution with a value of 367.7. This technical response is integrated with the Codification Subdistribution which is used as the basis for developing new application designs according to the stages in the SDLC method. The final result of this research is a new codification application system that is integrated with applications in the KRI and applications in the Codification Sub-Office so that it is expected to facilitate input of request data from ships and can shorten the time for requests to receive (PUT) in the provision support process. Keywords: Codification System Application, provision support, Quality Function Deployment (QFD) and System Development Life Cycle (SDLC).